What is new about hallux rigidus? - Viladot-Pericé, Ramón; Viladot Voegeli , Antonio (Journal of the Foot & Ankle, 2021)
Hallux rigidus (HR) represents one of the most frequent forefoot disorders, together with hallux valgus and lateral toe deformities, being the most frequent degenerative process in the foot and ankle. This publication is the result of the collaboration of colleagues of the Spanish Society of Medicine and Foot and Ankle Surgery (Sociedad Española de Medicina y Cirugía del Pie y Tobillo, SEMCPT) and the Argentinean Society of Medicine and Foot and Leg Surgery (Sociedad Argentina de Medicina y Cirugía de Pie y Pierna, SAMCPP). It is an honor for us to have this work edited in the Journal of the Foot & Ankle, a journal with a marked Latin identity. We really thank Alexandre Leme Godoy-Santos, Chairman of the Editorial Board, for his help and contribution. This update topic has been coordinated by R. Viladot Pericé and A. Viladot Voegeli, together with M. Herrera and M. Núñez-Samper. Considering the interest and the extent of this topic and, according to the coordinators, we have divided the publication into two parts. The first one describes general aspects (definition, etiology, classification, treatment algorithm, etc.) and the conservative treatment of HR, whereas the second one addresses the different surgical techniques described to treat this disease. The aim of this work is to review our knowledge on HR and to perform an update on the innovations that have emerged during the last years.